Analisis Kinerja Membran PVC-TiO2 dengan Variasi Waktu dan Tekanan Operasi dalam Mereduksi TDS, Kekeruhan, dan Total Coliform pada Sungai Jagir - Adjani, Della Putri; Restu Hikmah Ayu Murti (Jurnal Serambi Engineering, 2025)
The Jagir River has experienced a decline in water quality due to domestic and industrial activities, with pollutant parameters such as TDS, turbidity, and total coliform exceeding the quality standards. This study aims to analyze the effect of operating time and pressure variations of PVC- TiO2 ultrafiltration membranes on the removal capability of TDS, turbidity, and total coliform parameters as well as the flux rate of the membrane. The addition of TiO2 aims to increase the flux rate of the UF membrane. This research method involves adsorption pre-treatment using granular activated carbon (GAC) before the ultrafiltration process with varying pressures (1; 1.5; 2 bar) and operating time (15 – 75 minutes). The results showed that adsorption pre-treatment was able to reduce turbidity (95.45%), total coliform (59.93%), and TDS (18.89%). The combination of 2 bar pressure with an operating duration of 75 minutes resulted in the highest removal efficiency for all three parameters, namely total coliform (100%), turbidity (96.90%), and TDS (18.84%). TiO2 coating increases the membrane flux rate at the start of operation, especially at high pressures, but over time it decreases drastically due to fouling.